Moral federalism - Eckhard Janeba (Center for Economic Studies and ifo Institute (CESifo), 2004)
Many political issues like abortion, gay marriage or assisted suicide are strongly contested because individuals have preferences not only over their own choice but also about other individuals? actions. How should society decide these issues? This paper compares three regimes (centralization, decentralization and federalism) in an economy where individuals choose their residence and vote over a single-dimensional regulatory policy at the regional and national level. The main results are: (i) A move from decentralization to federalism, called moral federalism, is welfare improving behind the veil of ignorance if and only if centralization dominates decentralization, and (ii) for the group that favors a restrictive policy moral federalism is the more attractive the smaller its group size (subject to being the majority group), the larger the suffering from a given policy, and the smaller the regions? weight in determining the federal policy limit. The results are consistent with the Bush administration's attempt to restrict liberal policy choices at the state level after its narrow election victory in 2000.
Keywords: D7; H1; 330; federalism; decentralization; Tiebout equilibrium; consumption externality; morals; Meritorisches Gut; Ethik; Konsuminterdependenz; Föderalismus; Dezentralisierung; Institutioneller Wettbewerb; Abwanderung und Widerspruch; Theorie